Inflammatory Bowel Diseases and Irritable Bowel Syndrome: Overlap of Two Nosological Forms or Two Variants of the Same Disease? - A. A. Sheptulin; K. E. Vinogradskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To review available literature data on the relationship between inflammatory bowel disease (IBD) and irritable bowel syndrome (IBS).Key findings. Current publications on IBD and IBS present different viewpoints on their relationship. Thus, researchers have noted a high incidence of IBD against the background of IBS, frequent persistence of IBS-like symptoms after achieving IBD remission, as well as the possibility of overlapping the diseases. According to literature data, IBD and IBS should be treated as different forms of the same disease. An opinion is expressed that IBS-like complaints in patients with IBD remission should be considered as a separate disease referred to as “irritated inflammatory intestinal syndrome”. Treatment of IBS-like symptoms in patients with IBD remission has thus far not been developed.Conclusion. The problem of the relationship between IBD and IBS is currently controversial, thus requiring further clarification.